(untitled) (Communication & Society, 2024)
Speculative fiction is based on one main question: what if? This paper addresses the question of how audiences interpret such interrogative. In particular, our main interest lies in knowing how the different political ideologemes that may inhabit speculative fiction are signified. Thus, in this study we have focused on the genre of dystopia. To this end, a total of five focus groups were carried out. Specifically, the ideologemes tested in the reception study belong to socialism, conservatism, neoliberalism, liberalism and religious fundamentalism. The significance of these ideological values is empirically grounded in extensive qualitative research.